Jejak Historis dan Pengaruh Gereja Nestorian di Indonesia terhadap Perkembangan Kekristenan di Asia - Waruwu, Rikias Gulo (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2025)
This study examines the role of the Nestorian Church in the spread of Christianity in Indonesia and its impact on the development of Christianity in Asia. The main issue explored is the historical traces of the Nestorian Church in Indonesia, particularly in the port of Barus, and its influence on the growth of Christianity in Asia. The aim of this research is to explore the history of the Nestorian Church in Indonesia and Asia, as well as identify their cultural and social contributions. The research uses a qualitative approach with a historical method, where data is obtained through literature study from primary and secondary sources, and analyzed using content analysis. The findings reveal that, despite their limited influence in Indonesia, the Nestorian Church played an important role in introducing Christianity through trade routes, especially in China and Indonesia. In conclusion, while facing challenges and limited impact, the Nestorian Church made a significant contribution to the spread of Christianity in Asia, with social and cultural effects that warrant further attention.